Impact of stent edge dissection detected by optical coherence tomography after current-generation drug-eluting stent implantation. - Hiroyuki Jinnouchi (Public Library of Science (PLoS), 2021)
Background Stent edge dissection (SED) is a well-known predictor of worse clinical outcomes. However, impact of SED after current-generation drug-eluting stent (DES) implantation remains unknown since there was no study using only current-generation DES to assess impact of SED. This study aimed to investigate a relationship between SED detected by optical coherence tomography (OCT) and clinical outcomes after current-generation DES implantation. Methods This study enrolled 175 patients receiving OCT after current-generation DES implantation. The SED group was compared with the non-SED group in terms of the primary study endpoints which was the cumulative incidence of major adverse cardiac event (MACE) composed of cardiac death, target vessel myocardial infarction (TV-MI), and clinically-driven target lesion revascularization (CD-TLR). Results Of 175 patients, SED detected by OCT was observed in 32 patients, while 143 patients did not show SED. In the crude population, the SED group showed a significantly higher incidence of CD-TLR, definite stent thrombosis, TV-MI and cardiac death relative to the non-SED group. After adjustment by an inverse probability weighted methods, the SED group showed a significantly higher incidence of MACE compared with the non-SED group (hazard ratio 3.43, 95% confidence interval 1.09-10.81, p = 0.035). Fibrocalcific or lipidic plaques, greater lumen eccentricity, and stent-oversizing were the predictors of SED. Conclusions SED detected by OCT after the current-generation DES implantation led to unfavorable outcomes. Aggressive post-dilatation around the stent edge might worse clinical outcomes due to SED, although achievement of optimal stent expansion is strongly encouraged to improve clinical outcomes.